The Development of A Mobile-Based Application for TDI Café’s Food Ordering and Management using an Object-Oriented Approach - Selvamani, Khausalya; Mohd Zin, Nur Ariffin (Applied Information Technology And Computer Science, 2024)
TDI Café: Mobile-Based Application for Food Ordering and Management is a mobile-based application that improves the quality of the existing system in TDI Café by using a more advanced food ordering application. Since TDI Café still uses the traditional food order method as the ordering process. Therefore, the proposed application is specially developed for TDI Café owner, café workers, and customers. Furthermore, the TDI Cafe application can be run more systematically, save time, update order details and meet customer satisfaction. The application is designed using an object-oriented approach and the model used is the prototype model to develop the application. In addition, the application is developed using Android Studio and Firebase. Finally, it is expected that TDI Café Application can be used and benefit the users. In addition, the application can increase efficiency in making the food ordering processes effective using mobile devices.